The effect of MS media strength and cytokinin in the induction of shoots from shoot tip explants of Australian Finger Lime (Citrus australasica cv. Tasty Green) - Dahmendra Sriskanda,; Poi, Khoy Siong; Najwa Amalina Haradzi,; Nurulhikma Md Isa,; Sreeramanan Subramaniam,; Chew, Bee Lynn (Penerbit Universiti Kebangsaan Malaysia, 2021)
The Australian Finger Lime (Citrus australasica) is a type of citrus from the Rutaceae family, endemic to the east coast of Australia. The finger lime, loaded with numerous vitamins and renders a unique taste, has also been backed by science to contain essential amounts of antioxidants that are beneficial for cell protection, immune response, cancer prevention, ageing, arthritis and prevention of kidney stones. Current propagation attempts still rely on conventional methods that are less efficient and resulted in the slow establishment of farms for finger lime especially for commercialization purposes. This study focuses on the induction of shoots from shoot tip explants using 6-Benzylaminopurine (BAP) and Kinetin. Aseptic explants were inoculated into Murashige and Skoog (MS) medium of full-strength and half-strength followed by full-strength MS media supplemented with different concentrations of BAP and Kinetin. Results obtained in this study showed no significant differences in terms of the number of axillary shoots produced between explants cultured in full and half-strength MS media. However, the highest number of shoots and increment in shoot length were obtained from MS media supplemented with 2.0 mg/L BAP with the values 1.80 ± 0.27 and 2.56 ± 0.36 cm, respectively. In conclusion, MS media supplemented with 2.0 mg/L BAP was found optimal in the induction of shoots and shoot elongation of C. australasica cv. Tasty Green.